An Analysis of English Teacher’s Teaching Strategy in English in New Normal Era (A Study Conducted at SMA Negeri 1 Telaga) - Sindi Ivanka Towapo; Sartin T. Miolo; Nurlaila Husain (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study explores the teaching strategies employed by English teachers at SMAN 1 Telaga in adapting to the "new normal" era post-COVID-19. Using a descriptive qualitative research method, data were gathered through structured questionnaires from three experienced English teachers. The study identifies key strategies, including the integration of technology such as Google Meet, Zoom, and WhatsApp, as well as innovative teaching methods like role-playing, audiovisual media, and group discussions. The findings indicate that these strategies effectively increased student engagement. However, several challenges were encountered, including unstable internet connections, low student motivation, and limited access to digital devices. Teachers also faced difficulties in assessing students’ understanding in an online or hybrid learning environment. Despite these obstacles, institutional support, such as training on digital tools and infrastructure development, played a crucial role in facilitating effective teaching. To enhance English teaching in the post-pandemic era, this study recommends the further integration of interactive platforms, project-based learning, and blended learning approaches. Schools should also conduct regular training sessions for teachers to improve their digital literacy and pedagogical skills. Additionally, fostering a more interactive and student-centered learning environment can help address motivation issues. This research provides valuable insights into adapting English teaching strategies to overcome digital and motivational barriers, ensuring a more effective and engaging learning experience in the new normal era.